Clinical features and short-term prognosis in the very elderly, >90 year-old, patients hospitalized with heart failure. A population-based study (2016–2019). (3rd October 2022) - Anguita Gamez, M; Esteban, A; Bonilla, J L; Garcia, M; Bernal, J L; Del Prado, N; Fernandez Perez, C; Gomez Doblas, J J; Perez Villacastin, J; Marin, F; Elola, F J; Anguita Sanchez, M
Abstract: Background: Heart failure (HF) is a main health problem in western countries, and a major cause of hospitalizations and death, particularly in older people. Few data are available about clinical features and prognosis of very old patients, those aged 90 or more years. Purpose: To analyse the clinical features and short-term prognosis (in-hospital mortality and 30-day readmission rate) of patients aged 90 or more years hospitalized with HF in Spain in the last years. Methods: We conducted a retrospective analysis of patients discharged with an ICD-10 main diagnosis of HF from the Spanish National Health System (SNHS) public hospitals between 2016 and 2019, using as source of data the Minimum Basic Data Set of the SNHS. A comparison of clinical profile, in-hospital mortality and 30-day cardiovascular readmission rate between patients aged 75 to 89 years and those with 90 or more years was performed. Results: From 2016 to 2019, 354, 792 episodes of people older than 74-year and principal diagnosis of HF were included, being 59.2% female. Mean age of the whole population was 85.2±5.5 years, crude in-hospital mortality rate was 12.7% and crude cardiovascular 30-day readmission rate, 11.8%. The very older patients' subgroup (90 or more year-old) comprised 78.777 patients (22.2%). Table 1 shows the differences in clinical features between these patients and those aged 75 to 89 (77.8%). Patients aged 90 or more years were female in a higher proportion and showed a higher prevalence of cognitive impairment and renal failure, but a lower prevalence of most comorbidities (coronary artery revascularization, valve heart disease, cancer, diabetes mellitus, chronic liver disease). The diagnosis of previous myocardial infarction, stroke and systemic hypertension was similar in both groups (Table 1). Crude 30-day cardiovascular readmission rate was slightly but significantly lower in the oldest subgroup (10.9% vs 12%, p<0.001), while crude in-hospital mortality was higher (18.5% vs 11%, p<0.001). Conclusions: Patients aged 90 or more years represents almost a fourth part of elderly patients hospitalized with HF in Spain within the last years. In general, prevalence of comorbidities and associated heart disease was similar or lower, but in-hospital mortality was twice higher, as compared with less older patients. Funding Acknowledgement: Type of funding sources: None.